Correlation of radon anomalies with microseismic events in Kangra and Chamba valleys of N-W Himalaya - Rajiv Kumar; Naresh Kumar; Anand Kumar Sharma; Vivek Walia; H.S.Virk (Geofísica Internacional, 2000)
Radon monitoring was carried out at Palampur and Dalhousie stations in Kangra and Chamba valleys using emanometry for discrete measurements of time-series radon data since 1992 under Himalayan Seismicity programme of Government of India. The correlation of radon data with micro-earthquakes recorded by Indian Meteorological Department (IMD) network during the time window 1992-1997 shows a rising trend both in microseismicity as well as radon in Kangra and Chamba valleys of N-W Himalayan region under investigation.The effect of meteorological parameters (temperature, rainfall, humidity and wind velocity) on radon emanation was studied. The correlation co-efficients of radon data and the meteorological parameters recorded at Palampur suggest that temperature, rainfall and humidity have positive correlation, whereas wind velocity has negative correlation with radon.